Dwelling in Transience: Kyai, Pesantren, and the Circulation of Piety among Indonesian Migrants in Malaysia - Wong, Diana; Aziz, Arfan (Kontekstualita: Jurnal Penelitian Sosial Keagamaan, 2011)
This article explores the religious life of Indonesian migrants in Malaysia. The study was conducted in a village in Selangor State. On the basis of informantsâ request, the real name of informants and places are not exposed. This study used ethnography, survey, and in-depth interview as techniques for data collection. The author lived with the migrants for about four years (2006-2010). The majority of migrants in the area are from East Java, especially from Lumajang, Jember and Madura, areas which are highly influenced by religious culture of Nahdatul Ulama. After immersing into their religious life, this study reveals three important topics of interest: religious ritual activities, piety, and relations between migrants and religious figures from their homeland. Although kyai and religious leaders are not physically present with the migrants, the migrants developed their own religious life. They create new religious figures or invite kyai, lora and habib who come to Malaysia for commercial or travel purposes to guide them. To a certain degree, the migrants are trying to defend their santri tradition amid the local governmentâs pressures on their status as illegal migrants.